An evaluation of the Quezon City Science High School (QCSHS) library compliance with DECS standards and curriculum requirements - Mabalot, Adalia L. (2010)
This study was conducted to assess the present condition of the QCSHS Library's compliance with the DECS Standards on the following areas: physical set up, furniture and equipment, collection, personnel/staff and library service. Library collection was further examined to determine if it meets the curriculum needs of a science, mathematics and technology-oriented hugh school. Collection mapping was accomplished based on the RSHS QCSHS curriculum using Loertscher's collection mapping technique along with shelflist count.Integrating the curriculum and the completed collection map gauged, identified and presented the strengths and weakness of the collection.